Influence of surface treatments in flexural strength and superficial topography of a lithium disilicate ceramic - Rossi, Natália Rivoli [UNESP]; Sato, Tabata do Prado [UNESP]; Marinho, Caroline Cotes [UNESP]; Macedo, Vanessa da Cruz [UNESP]; Paes Junior, Tarcísio José de Arruda [UNESP]; Kimpara, Estevão Tomomitsu [UNESP] (Editora Cubo, 2019)
Objective: The aim of the study was to evaluate the influence of different surface post-etching treatments in flexural strength, contact angle and surface roughness of a lithium disilicate ceramic. Material and Methods: 60 bars (16 × 2 × 4 mm) were divided in six groups (n=10): C, no treatment; HF, hydrofluoric acid for 20 s (HF) + washing (60 s), drying (30s); HFL, HF + washing (60 s), drying (30 s) and luting; HFNL, HF + washing (60 s) + neutralization with sodium bicarbonate (SB) for 40 s + washing (5s), drying (30 s) and luting; HFUL, HF + washing (60 s) + ultrasonic bath (UB) for 4 min, drying (30 s) and luting; HFNUL, HF + washing (60 s) + SB (40 s) + UB (4 min) and luting. The bars were submitted to three-points flexural strength test. 25 ceramic blocks (12 × 7 × 7 mm) were divided into five groups (n=5) to evaluate roughness and contact angle C - no treatment; HF - HF; HFU - HF and UB for 5 min; HFN - HF and SB; HFNU - HF, UB and SB. A scanning electron microscope (SEM) showed the surface of the samples. ANOVA one-way statistical analysis was done for comparison of results. Results: There was no statistical difference for flexural strength (p-value = 0.15) and for surface roughness (p-valor = 0.15). However, it was obtained statistically significant difference for contact angle (p-valor = 0.00). SEM images showed precipitates after the acid etching, which were removed by post-etching treatments. Conclusion: It can be concluded that the different post-etching surface treatments did not increase the flexural strength, surface roughness, but it influenced the ceramic wetting and SEM images.
Influência dos tratamentos de superfície na resistência à flexão e na topografia superficial de uma cerâmica de dissilicato de lítio
Keywords: Contact angle; Hydrofluoric acid; Lithium disilicate; Scanning electron microscope; Surface roughness; Ultrasonic bath